ANALYSIS OF THE EFFECTIVENESS OF THE IMPLEMENTATION OF THE PLENARY MEETINGS OF THE REGIONAL PEOPLE’S REPRESENTATIVE COUNCIL (DPRD) OF BANDAR LAMPUNG CITY - Siti Afni; Malik (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the effectiveness of the implementation of sessions and meetings of the Bandar Lampung City Regional People's Representative Council. All data were obtained directly from informants in the field using interviews and document studies. The results of the study indicate that, based on the analysis, it can be concluded that the effectiveness of the implementation of sessions and meetings of the Bandar Lampung City Regional People's Representative Council according to the dimensions of (a) Goal Attainment is not optimal. (b) Integration: Meeting effectiveness is hampered by weak coordination between Regional People's Representative Council organs. (c) Adaptation: The Regional People's Representative Council is still less responsive to change. (d) Productivity: The implementation of trials and meetings has not yet produced output commensurate with the resources.